The Pink Tank in the Room: The Role of Religious Considerations in the Discussion of Women’s Combat Service—The Case of the Israel Defense Forces - Rosman, Elisheva (Religions, 2020)
Women serve in diverse roles in the 21st century militaries of the world. They are no longer banned from combat. The presence of women on the battlefield has raised religious arguments and considerations. What role do religious arguments play in the discussion regarding women’s military service? Using media, internal publications, as well as academic articles, the current paper examined this question in the context of the Israel Defense Forces (IDF): a conscription-based military that conscripts both men and women, religious and secular, for both combat and noncombat postings. Using the case of the pilot program in the IDF attempting to integrate women in the Israeli tank corps, as well as gauging the way religious men view this change, the paper argues that religious considerations serve the same purpose as functional considerations and can be amplified or lessened, as needed.